PERUBAHAN TINGKAT INFLASI DAN PENDAPATAN TIDAK KENA PAJAK TERHADAP PENERIMAAN NEGARA - Rahmawati Rahmawati (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
These research purposes for knowing the influence change of inflation rate and nontax revenue (PTKP) to the state income from tax revenue (PPh 21). Data that has used in this research are primary and secondary which has taken from DJP, BPS and other relevant sources. This data used classic assumption test and multiple linear regressions. Research result showed that the changing of inflation rate and changing of nontax revenue (PTKP) had a significant effect to state income. Although mathematically the increasing of nontax revenue (PTKP) should decrease state income from tax, according to this research, the increasing of nontax revenue (PTKP) otherwise also increasing state income from tax. These mean that the government policy for increasing nontax revenue (PTKP) already correct policy.DOI: 10.15408/sjie.v2i1.2374